Interpreting the Image on the Konda Plaque - L. N. Ermolenko (Вестник Кемеровского государственного университета, 2020)
The research featured the authentic composition on a IX–XX century plaque found near the Konda River. The article focuses on some ambiguous details of the image. For instance, the decoration of the female figure’s clothing is made up of several zones. Its motifs include scales and dots, which are known to represent animal hair in metalwork and ceramics. In general, the image revealed a certain parallelism in the ornamentation of human clothing, animal hair, and bird plumage. The author established a clear correlation between the zoning and motifs of the female dress and the stylized plumage of ornithomorphic creatures in Oriental toreutics. Therefore, the clothes the male character is trying to take off the woman may symbolize avian plumage. The author interpreted the plot depicted on the Konda plaque as the motif of stealing the avian gown of the peri, a mythical creature of medieval Asian folklore. According to legends, the hero had to steal peri’s clothes to marry her. Thus, the image of peri, which was popular in verbal folklore, proved to be quite common in visual art as well, in particular, in early Islamic art.